Influence of InGaN layer growth temperature on luminescence properties of InGaN/GaN multiple quantum wells. (23rd February 2018) - Wang, Xiaowei; Yang, Jing; Zhao, Degang; Jiang, Desheng; Liu, Zongshun; Liu, Wei; Liang, Feng; Liu, Shuangtao; Xing, Yao; Wang, Wenjie; Li, Mo
Abstract: Optical investigation was performed on InGaN/GaN multiple quantum well (MQW) structures grown by metalorganic chemical vapor deposition (MOCVD) with different temperatures. It is found that the emission intensity decreases abruptly when the growth temperature of InGaN QW decreases from 710 to 670 °C. The XRD measurements show that a poorer quality interface between the QW layers could decrease the emission quite a bit when the growth temperature is lower. In addition, due to the weakening surface mobility of adatoms, the localization states accompanied with defects are distributed more inhomogeneous at lower growth temperature, which is also responsible for the low emission intensity.